2020
DOI: 10.3390/brainsci10050276
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Combined Transcranial Direct Current Stimulation with Cognitive Training in Girls with Rett Syndrome

Abstract: Background: Transcranial Direct Current Stimulation (tDCS) combined with traditional rehabilitative techniques has not been widely applied to Rett Syndrome (RTT). The aim of this study was to examine the effects of combined cognitive traditional training with tDCS applied to attention and language measures in subjects with RTT. Methods: 31 subjects with RTT were randomly allocated into two groups: non-sham tDCS (n = 18) and sham tDCS (n = 13). The former received the integrated intervention non-sham tDCS plus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 45 publications
(52 reference statements)
2
17
0
Order By: Relevance
“…TDCS combined with a rehabilitation technique also increased the absolute power of theta, alpha and beta bands in patients’ resting EEG. The increase in theta power reflects some worsening of EEG and was not reproduced in a recent tDCS study by the same research team [ 221 ] that included 31 RTT patients, and was carefully designed to compare tDCS effects in non-sham and sham control groups. Other results were reproduced and pointed to the improvement of behavioral and neurophysiological functions.…”
Section: Resultsmentioning
confidence: 99%
“…TDCS combined with a rehabilitation technique also increased the absolute power of theta, alpha and beta bands in patients’ resting EEG. The increase in theta power reflects some worsening of EEG and was not reproduced in a recent tDCS study by the same research team [ 221 ] that included 31 RTT patients, and was carefully designed to compare tDCS effects in non-sham and sham control groups. Other results were reproduced and pointed to the improvement of behavioral and neurophysiological functions.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Stasolla et al ( 2021 ) developed new virtual reality-aided solutions to remotely evaluate and recovery cognitive functioning among individuals with neurodegenerative diseases to promote cognitive empowerment (Fabio et al, 2020 ). Internet access and leisure option were embedded in patients with neurological disorders.…”
Section: Discussionmentioning
confidence: 99%
“…This requires technological support based on gaze tracking to allow for interaction with other people and with other technological platforms (Caprì et al, 2020a ). From the psychological point of view, studies examining the effectiveness of multimedia technologies have demonstrated positive effects on the cognitive, communicative and motivational abilities of children with RTT (Fabio et al, 2018c , 2020b ). In particular, it was found that multimedia presentations activate motivational factors which, in turn, increase the attention levels of patients with RTT.…”
Section: Introductionmentioning
confidence: 99%